Carbon Footprint Analysis for Biomass-Fueled Combined Heat and Power Station: A Case Study - Yingying Zheng; Chang Liu; Jie Zhu; Yuanrui Sang; Jinglong Wang; Wenjing Zhao; Minghao Zhuang (Agriculture, 2022)
Biomass could substitute fossil fuels in heat- and power-generation projects to reduce air pollution and greenhouse gas from many stages of the life cycle. The Nordjylland Power Station, one of Denmark’s largest power plants, is a 100% coal-fired combined heat and power plant. To reduce carbon dioxide emissions, this power plant is converting to be 100% biomass-fueled. However, biomass cannot be assumed as an emission-free energy source, even though it has certain advantages in terms of carbon sink capability. The environmental impacts among various biomass sources are unclear. Wheat straw and wood pellets are two of the most abundant biomass resources in Denmark. In this study, by conducting a screening life-cycle assessment, the expected savings of global warming potential emissions due to the substitution of coal with wheat straw or wood pellets are quantified. The life-cycle assessment’s results indicate that for producing 1 MJ of heat, the carbon dioxide equivalent from coal, wheat straw, and wood pellets are 117.01, 22.73, and 78.19 g, respectively. The combustion stage accounts for most of the carbon dioxide emissions. The recommendation is that wheat straw is preferred over wood pellets in terms of carbon emissions based on the current assumptions.